PENGEMBANGAN USAHA KERAJINAN ROTAN (PENDEKATAN ACTION RESEARCH) STUDI KASUS DI UKM ASRI ROTAN DESA TRANGSAN, KECAMATAN GATAK, KABUPATEN SUKOHARJO - Kawiji Kawiji; Nuning Setyowati (Asian Journal of Innovation and Entrepreneurship, 2013)
SMEs of Asri Rotan has economic potential, but also has disadvantages such as limited technology and business management weaknesses. This study aims to analyze the advantages potential, formulating business development strategies for SMEs Asri Rotan and followed up with partisipatory action as realization of the development strategies. This study uses a participatory action approach and using the primary database include revenue, costs, internal factors (strengths-weaknesses) and external factors (opportunities-threats). The analysis tools are profit analysis and SWOT Analysis. Results showed that SMEs Asri Rattan is profitable and feasible to developed. Alternative development strategies for SMEs Asri Rattan include: Maintaining the quality of products to enhance product competitiveness, establish partnerships with agents to maintain continuity of supply and demand, increase the capacity of production technology, improving business management, optimum use of government support, increasing the skill and creativity of human resources for increased competitive advantage. Partisipative action as realization of development strategies include: training of simple bookkeeping, preparing financial report, preparing business plans, increasing production technology capacity.Keywords: SME of Asri Rattan, profit analysis, development strategies, action research